1960
DOI: 10.1002/cpt19601116
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of thiopental by body tissues and its relation to the duration of narcosis

Abstract: Department of Anesthesiology, Hospital of the University of PennsylvaniaIt is commonly believed that the anesthetic actions of thiopental are terminated, not by metabolism of the drug, but by its concentration in body fat.2 Thiopental t is highly fat soluble, 3 but it has not been shown that its uptake by adipose tissue occurs rapidly enough to account for the speed with which consciousness is regained after intravenous injection of the drug. We have attempted to study this point. 9 Our conclusion is that fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1967
1967
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(37 citation statements)
references
References 3 publications
(3 reference statements)
0
36
0
1
Order By: Relevance
“…The data were taken from the excellent figures found in the reference and the constants of the bi-exponential equations were estimated by the usual procedures. Many studies of thiopentobarbital have indicated that a more complex distribution model is required for an understanding of period of sleep induced by the drug relative to its distribution and metabolism (8,9). It appears from the data of Brodie et ul., however, that not more than a two-compartmental model is necessary to fit the available data, and if one were attempting to estimate the true absorption rate of the drug or assess its true elimination rate constant, that this model may be adequate.…”
Section: Resultsmentioning
confidence: 99%
“…The data were taken from the excellent figures found in the reference and the constants of the bi-exponential equations were estimated by the usual procedures. Many studies of thiopentobarbital have indicated that a more complex distribution model is required for an understanding of period of sleep induced by the drug relative to its distribution and metabolism (8,9). It appears from the data of Brodie et ul., however, that not more than a two-compartmental model is necessary to fit the available data, and if one were attempting to estimate the true absorption rate of the drug or assess its true elimination rate constant, that this model may be adequate.…”
Section: Resultsmentioning
confidence: 99%
“…Ghoneim and Van Hamme [31] suggested that thiopental elimination may be controlled by its distribution characteristics. It has now been fairly well demonstrated that thiopental is ultimately concentrated by body fat, which represents the deep compartment [32,33]. In humans, after a single bolus injection, thi0pental is concentrated in the adipose tissues in 1.5 to 2.5 h according to Shideman et al [34], or in 5 to 6 h according to Dayton et al [35].…”
Section: Discussionmentioning
confidence: 99%
“…These values are in good agreement with the equilibration time of the deep compartment, which was established by simulation (1.5 to 4 h) in our study. According to the Price et al study [33], fat comes into equilibrium more slowly, in 8 to 10 h after the drug injection. The values of V1 and Vss did not show any differences after single bolus and repeated doses.…”
Section: Discussionmentioning
confidence: 99%
“…After maintenance of anesthesia for several minutes to several hours, however, these drugs become widely redistributed in peripheral tissues, including the myocardium. [20][21][22] If there were a significant effect of anesthetics upon the determinants of electrical defibrillation, one might reasonably expect a gradual drift of the threshold voltage and current for defibrillation over the course of experiments using anesthetized animals as subjects. Control studies demonstrating the presence or absence of such a drift in defibrillation threshold over time intervals greater than one hour have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%